Aflati nr întregi x,y pentru care (x+1)×(y-2)=3
Răspunsuri la întrebare
Răspuns de
4
(x+1) x (y-2) = 3
x+1 = 3/y-2
(x+1) (y-2) totul / (y-2) = 3/(y-2)
x = 3-(y-2) / y-2
x+1-1 = 3/y-2 - 1
x = -y+2+3 / y-2
x = -y+5 / y-2
y-2 = 3/x+1
(x+1) (y-2) totul / (x+1)
y = 3+2x+2 / x+1
y - 2+2 = 3/x+1 + 2
y = 2x + 5 / x+1.
x+1 = 3/y-2
(x+1) (y-2) totul / (y-2) = 3/(y-2)
x = 3-(y-2) / y-2
x+1-1 = 3/y-2 - 1
x = -y+2+3 / y-2
x = -y+5 / y-2
y-2 = 3/x+1
(x+1) (y-2) totul / (x+1)
y = 3+2x+2 / x+1
y - 2+2 = 3/x+1 + 2
y = 2x + 5 / x+1.
Alte întrebări interesante
Istorie,
8 ani în urmă
Geografie,
8 ani în urmă
Biologie,
8 ani în urmă
Limba română,
9 ani în urmă
Geografie,
9 ani în urmă